Tensions of the Historiographic Traces of Brazilian Zouk - Navarro, Ana Carolina; Azevedo Gama Buarque, Isabela Maria; Luporini Menegaldo, Luciano (Revista Brasileira de Estudos da Presença, 2023)
This article aims to disseminate information about Brazilian Zouk and contribute to the historical understanding of Brazilian dances through critical reflection. To this end, we researched various bibliographic sources, such as articles, theses, dissertations, videos, and reports, in addition to personal notes. The analysis showed disputes concerning the following aspects: 1) the rise of the musical rhythm and dance; 2) the use of basic and competitive movements; 3) the process of commodification; and 4) contemporary issues related to the body. It is important to emphasize that this work is motivated by the necessity to broaden the debate on dance historiography in the country.